Measles—an ENT diagnosis? - Tiago Lourenço Coelho; Nuno Dias Silva; Hugo Figueiredo; Ricardo Caiado (Clinical Case Reports, 2023)
Key Clinical Message Ear, Nose and Throat (ENT) should remain vigilant about the emergence of measles in non‐endemic countries. Clinical suspicion is crucial in identifying this disease, with Koplik's spots being a pathognomonic sign. Forming part of the differential diagnosis and helping to prevent potential outbreaks.